2011
DOI: 10.1061/(asce)em.1943-7889.0000289
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Concrete Crack Width under Combined Reinforcement Corrosion and Applied Load

Abstract: TABLE OF CONTENTS vi LIST OF FIGURES xi LIST OF TABLES xvi NOTATION xvii CHAPTER 1 INTRODUCTION 1.1 Background xix c f Concrete strength in compression ,0 c f Strength of zero porosity ' t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 90 publications
(132 reference statements)
0
55
0
Order By: Relevance
“…Balafas and Burgoyne [13] proposed a double-cylinder model based on the fracture mechanics theory to determine structural lifetime from corrosion initiation to cover spalling. Li et al [14][15] assumed that the cracked concrete cylinder was an isotropic material with a reduced elastic modulus in the tangential direction. However, the stress continuity and strain compatibility conditions on the common boundary between the uncracked and cracked concrete cylinders were not satisfied in their model.…”
Section: Introductionmentioning
confidence: 99%
“…Balafas and Burgoyne [13] proposed a double-cylinder model based on the fracture mechanics theory to determine structural lifetime from corrosion initiation to cover spalling. Li et al [14][15] assumed that the cracked concrete cylinder was an isotropic material with a reduced elastic modulus in the tangential direction. However, the stress continuity and strain compatibility conditions on the common boundary between the uncracked and cracked concrete cylinders were not satisfied in their model.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies and engineering investigations on corroded RC, many scholars including Li and Yang [1], Ma et al [2] and Wang and Liang [3] found that the transverse rebar could undergo more severe damage than the longitudinal rebar, and even break at the junction point with the longitudinal rebar. Because of the comparative smaller depth of concrete cover for transverse rebars, the latter are more easily reached by chloride and other corrosion induction chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reinstatement cost of corrosion-affected RC structures is significantly high; 36 worldwide, the maintenance and repair costs for corrosion-affected concrete infrastructure are 37 estimated around $100 billion per annum [1]. 38 …”
Section: Introduction 29mentioning
confidence: 99%
“…Fracture energy 120 N/m S 1 Spacing between rebars 30 mm S 2 Spacing between rebars 45 mm S 3 Spacing between rebars 60 mm P Crack pattern De Delamination Sp Combined delamination and corner spalling t th1…”
mentioning
confidence: 99%
See 1 more Smart Citation